ANALISIS PENGARUH SUKU BUNGA TERHADAP KREDIT USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA BANK PEMBANGUNAN DAERAH (BPD) DI PROVINSI JAMBI - Isnain Effendi (Universitas Batanghari Jambi, 2016)
Monetary policy is one of wisdom that can affect a country’s economy, banking is a medium that limits between sector moneter with sectorial. Development of SME loans in regional development bank’s, the highest growth in 2008 at 41 % le diangka Rp. 5,197.687 M and the lowest in 2011 with growth of 31 % dianggka Rp. 4.489.554 M with an average growth of Smes given BPD Jambi Province amounted to 17,22 %, from the regression resultsw are negative and significant impact on the interest rate credit. Keyword : the influence of interest rates, UMKM, the development of the area of jambi province